Translation Techniques and Their Impacts to the Modality Orientationâ€™s Shift in The Jungle Book Movie Subtitle - Romdhati, Arifah Tenny; Nababan, Mangatur; Santosa, Riyadi (Lingua Cultura, 2018)
This research aimed to analyze the translation techniques used by the subtitler to translate modality orientation and the impact of the translation techniques on the modality orientation shifts in â€œThe Jungle Bookâ€ movie subtitle. This research was a descriptive qualitative research. The data in this research were words, phrases, and clauses as the marker of modality orientation in the movie, and translation techniques used by the subtitler. Modality orientation was obtained through content analysis based on Systemic Functional Linguistics (SFL) theory as proposed by Halliday and Matthiessen (2014). Then, translation techniques were obtained through Focus Group Discussion (FGD) as proposed by Molina and Albir (2002). The findings show that the subtitler uses seven techniques to translate modality orientation. They have established equivalence, modulation, discursive creation with established equivalence, deletion, transposition, discursive creation, and reduction with established equivalence. The subtitler uses established equivalence to translate orientation that produces same category, value, form, and orientation. Deletion technique, modulation, and creation discursive with established equivalence cause the loss of modality in the target language. Applying modulation, transposition, discursive creation, and reduction with established equivalence techniques make a shift on the modality orientation and also produce different meaning in the target language. The change of value in modality in the target language is caused by the use of modulation and reduction with established equivalence technique by the subtitler.